Clay minerals evidences for cold-warm fluctuations in the Early Silurian - Zhibo Zhang; Jiaming Zhang; Hengye Wei; Huan Li; Yinghai Guo; Chunlin Zeng (PLoS ONE, 2025)
The Late Ordovician and Early Silurian transition is an important period of geological evolution, attracting increasing attentions. However, the cause for the biotic recovery from the end-Ordovician mass extinction has remained controversial. A set of black shales deposited in the Longmaxi Formation of the Early Silurian recorded the characteristics of the climate evolution after this extinction event, which played a crucial role in the biological recovery. In this paper, the shale of the Longmaxi Formation(LMX Fm.) in Well Yucan-6, Sichuan Basin is selected to analyze total organic carbon (TOC) and clay mineral composition, so as to address the climate evolution and its implications for the biotic recovery. The results show that the TOC content in the shale is higher at the bottom of the Longmaxi Formation in Well Yucan-6, and gradually decreases upward; the clay minerals are dominated by chlorite, illite, illite/smectite and chlorite/smectite mixed layer minerals, with no kaolinite and montmorillonite minerals being found. The clay minerals are mainly composed of illite/smectite mixed layer mineral with subordinate minerals of illite and chlorite, and a mall amount of chlorite/smectite mixed layer. Based on the characteristics of the illite and chlorite contents, and the ratios of illite/chlorite (I/C) and (smectite illit/smectite mixed layer mineral)/(illite+chlorite), i.e., (S + I/S)/(I + C), the paleoclimate evolution process of the Longmaxi Age is divided into three stages. Stage 1 is a climate evolution period of dry-wet, cold-hot rhythms; Stage 2 is a warm and humid climate evolution period, without obvious change in TOC content; and Stage 3 is a dry and cold climate evolution period, without obvious change in TOC. When combining these study results with the characteristics of the inorganic carbon isotope change trend in Silurian Epoch in the Tibet area and the whole world, the following conclusion has been drawn: The Early Silurian Longmaxi Age in Sichuan Basin was generally in a dry and cold environment, consistent with the characteristics of global paleoclimate evolution. These further indicates that the biotic recovery was delayed by the dry and cold climatic conditions in the earliest Silurian following the Hirnantian glaciation. Until the relative warm and cold climatic conditions in the early Silurian, biotic recovery started with the ameliorative environments.